PENGARUH MODEL PEMEBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII UPTD SMP NEGERI 5 PEMATANGSIANTAR - Sinaga, Sanni; Tambunan, Lois Oinike; Sidabutar, Ropinus (Universitas Islam Sumatera Utara, 2025)
This study aims to determine the effect of guided inquiry learning models on students' mathematical problem-solving abilities in probability. The research population consisted of all eighth-grade students at UPTD SMP Negeri 5 Pematangsiantar in the 2025/2026 academic year, while the research sample was taken randomly and consisted of treatment classes that used guided inquiry learning models. The research instruments consisted of a mathematical problem-solving ability test and a student perception questionnaire used to support the research data. Data analysis was performed using simple linear regression and t-tests. The results showed that there was a significant effect of the guided inquiry learning model on students' mathematical problem-solving abilities. The regression equation obtained was Y=1.596 + 0.311X with a coefficient value of b = 1.596. The t-test results showed that the guided inquiry learning model had a positive and significant effect on students' mathematical problem-solving skills in probability material.